Development of a functional electrical stimulator with feedback control / Nur Liyana Azmi - Nur Liyana , Azmi (2012)
Functional Electrical Stimulation (FES) is a means of passing small electrical impulses through nervous tissue of paralyzed muscles that is no longer controlled by patient. Its function is not only to improve impaired function but also to slow down or stop bone and muscle deterioration, and to improve circulation in paralyzed limbs of spinal cord injury (SCI) and stroke patients. However, the major limitation of FES is muscle fatigue. Moreover, most works on FES system are focussed on open loop mode which do not automatically regulate the desired output. Thus, closed loop FES system need to be developed. This research paper presents the work on developing a closed loop FES system or FES system with feedback control. The work is divided into two parts namely the development part and the experiment part. In the development part, a FES stimulator is constructed. The FES stimulator includes the high voltage power and the current closedloop control circuit. On the other hand, there are two sections in the experiment part. The first experiment uses a laboratory setting with beaker and oscilloscope to ensure the closedloop control is successful. The second part utilizes FES with real human muscle to be stimulated with the voltage stepped up to overcome skin resistance. This project also addressed the issue of varying the skin temperatures used as a feedback parameter of FES system as this work has not been investigated before.